Análise global-local de "risers" flexíveis - Rosas, João Carlos de Castro (1992)
An unified numerical tool for a global-local analysis of the structure mechanical behaviour of multi-layered flexible risers intended for offshore oil explotation is presented. A quasi-static geometric nonlinear analysis of the planar behaviour of these componentes is carried out for operational scenarios, considering long period excursion of a floating platform. Linear static analysis of the local behaviour including resultant strains and stresses in the unbonded layers are also made for selected spans over the riser length. The obtained numerical results from a typical component are used to demostrate that certain usual practical design and checking procedures may be sometimes overconservative and someother times underconservative. Finally, some simplifying assignments are forwarded for global analysis of an isolated flexible riser, and some necessary developments towards more refined calculations are underlined.